HUMAN BRUCELLOSIS AMONG PYREXIA OF UNKNOWN ORIGIN CASES IN TWO TERTIARY HOSPITALS, IN SANA'A, YEMEN - Maher, Ahlam Ali Ahmed; Al-Huraibi, Belques Sharaf; Al-Kholani, Abdulwahab Ismail Mohamed; Al-Dhafari, Omar Abdullah M; Al-Najhi, Mohammed Mohammed Ali; Al-Shamahy, Hassan Abdulwahab; Al-dossary, Omar Ahmed Esma’il; Al-Ankoshy, Azhar Azher Mohammed (Universal Journal of Pharmaceutical Research, 2022)
Background and objectives: Brucellosis continues a most important health problem in numerous parts of the world and in the Middle East regions is a significant origin of acute febrile illness. This study was conducted to determine Brucella antibodies among patients with PUO, the association of brucellosis with demographic characteristics, identify clinical symptoms and risk factors for Brucella infection among PUO cases. Materials and Methods: This cross-sectional research study was conducted in two health institutions; Al-Jumhouri Hospital and Al-Thawra Hospital, between January 2021 to January 2022. The required data were gathered from each patient by using pre-defined standardized questionnaire. Five mL of sterile whole blood was collected from each patient and then tested for Brucella antibodies using a standard tubular agglutination test. The data were then analyzed using the statistical software Epi Info version 6. Results: Among the 241 PUO patients, females were 72.2% and males 27.8%. The mean ± SD for total age was 28.8±15.8 years. The rate of Brucella antibody among patients with PUO was 29%, females 78.6% higher than males by 21.4%. Clinical characteristics of PUO patients were persistent fever (36.9%), intermittent fever (63.1%), sweating (63.5%), shivering (61.4%), joint pain (78.4%), muscle pain (78.4%), back pain (74.7) back head pain (66.4%), headache (60.4%), weight loss (52.9%), body weakness (89.2%), loss of appetite (50.6%), and nausea (46.1%). The risk factors for brucellosis among the PUO patients was handling of animals during parturition (69.2%, OR=7, p<0.0001). Conclusion: These findings revealed a high prevalence of human brucellosis among PUO patients in Sana'a city and will becoming a serious problem that threats the health care system in Yemen. So, awareness programs should be provided to doctors, population about Brucella infection and its risk factors. Peer Review History: Received: 2 December 2021; Revised: 8 January 2022; Accepted: 10 February, Available online: 15 March 2022 Academic Editor: Dr. Amany Mohamed Alboghdadly , Princess Nourah bint abdulrahman university, Riyadh, amalbgadley@pnu.edu.sa Reviewers: Dr. Bilge Ahsen KARA, Ankara Gazi Mustafa Kemal Hospital, Turkey, ahsndkyc@gmail.com Dr. Wadhah Hassan Ali Edrees, Hajja University, Yemen, edress2020@gmail.com